2015
DOI: 10.1002/hup.2486
|View full text |Cite
|
Sign up to set email alerts
|

Novel psychoactive substances: use and knowledge among adolescents and young adults in urban and rural areas

Abstract: Urban areas may represent a focal point for preventive strategies, given the presence of higher levels of NPS knowledge. Moreover, the association between binge-drinking habits and NPS use was really strong. This issue should not be underestimated because of its medical, psychopathological and social consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 23 publications
2
58
1
3
Order By: Relevance
“…As gambling behaviors were found to be largely affected by neighborhood accessibility to gambling opportunities [33], gaming behavior might also be affected by the widespread PC cafes or easier access to diverse game contents at metropolitan cities. A similar trend was found in users of novel psychoactive substances probably due to the more widespread opportunities to attend recreational settings such as discos and nightclubs, commonly located in urban areas [34]. …”
Section: Discussionmentioning
confidence: 54%
“…As gambling behaviors were found to be largely affected by neighborhood accessibility to gambling opportunities [33], gaming behavior might also be affected by the widespread PC cafes or easier access to diverse game contents at metropolitan cities. A similar trend was found in users of novel psychoactive substances probably due to the more widespread opportunities to attend recreational settings such as discos and nightclubs, commonly located in urban areas [34]. …”
Section: Discussionmentioning
confidence: 54%
“…cannabis use increases use of other illicit drugs) is debated. Associations between cannabis use and use of other illicit [5356] and novel psychoactive substances [5759] including temporal relationships between cannabis use and other illicit drug use[54, 6062] have been reported. A 25 year longitudinal study that conducted annual assessments of illicit drug use found that regular or heavy cannabis use was associated with an increased risk of using other illicit drugs[60], observations similar to other studies[63, 64].…”
Section: Methodsmentioning
confidence: 99%
“…The use of these substances is vanishingly rare in general population studies (Champion, Teesson, & Newton, 2015;Martinotti et al, 2015;Palamar, Martins, Su, & Ompad, 2015) and thus knowledge of consumption patterns is scarce. According to the Flash Eurobarometer 401 (European Commission, 2014), nearly two-thirds of participants that had used a NPS within the past 12 months had used it in the context of parties.…”
mentioning
confidence: 99%